Evolving Stark Effect During Growth of Perovskite Nanocrystals Measured Using Transient Absorption - Sadighian, James C.; Wilson, Kelly S.; Crawford, Michael L.; Wong, Cathy Y. (Frontiers in Chemistry, 2020)
Methylammonium lead triiodide (MAPbI3) nanocrystals (NCs) are emerging materials for a range of optoelectronic applications. Photophysical characterization is typically limited to structurally stable NCs owing to the long timescales required for many spectroscopies, preventing the accurate measurement of NCs during growth. This is a particular challenge for non-linear spectroscopies such as transient absorption. Here we report on the use of a novel single-shot transient absorption (SSTA) spectrometer to study MAPbI3 NCs as they grow. Comparing the transient spectra to derivatives of the linear absorbance reveals that photogenerated charge carriers become localized at surface trap states during NC growth, inducing a TA lineshape characteristic of the Stark effect. Observation of this Stark signal shows that the contribution of trapped carriers to the TA signal declines as growth continues, supporting a growth mechanism with increased surface ligation toward the end of NC growth. This work opens the door to the application of time-resolved spectroscopies to NCs in situ, during their synthesis, to provide greater insight into their growth mechanisms and the evolution of their photophysical properties.